Performance of gram (Cicer arietinum) under neem based agroforestry system in semi-arid region - Pandey, A.K.; Gupta, V.K.; Solanki, K.R. (Indian Journal of Agroforestry, 2020)
Tree-crop interface studies were conducted at National Research Centre for Agroforestry, Jhansi in a 4-year old neem (Azadirachta indica A. Juss) plantation to examine growth performance and productivity of neem trees and associated understorey crop-gram (Cicer arientinum ) over two years. The availability of photosynthetically active radiation (PAR) was highly correlated with vegetative growth and yield attributes of the crop. PAR decreased with increase in the age of the trees as reduction was 33% in 1998 and 48% in 1999 as compared to the open. The reduction in grain yield was 29% in 1998 and 40% in 1999 under the tree canopy which suggested that canopy manipulation of neem was required to enhance crop yield. Soil water and nutrients were not limiting factors for crop performance however crop growth and yield was lowest near to the tree base. Although crop yields under the tree canopy decreased but the increased wood volume and fruit yield of neem trees was more than reduced yield of understorey crop in term of money. Neem trees attained mean current annual increment (CAI) of 55.19 cm for tree height, 2.06 cm for dbh and 58.73 cm for crown diameter. The mean annual litter fall by neem trees was 2976 kg ha-1 at the density of 625 trees ha-1 with potential return of 50, 1.11, 13.18 and 58.33 kg ha-1 of available nitrogen, phosphorous, potassium and calcium, respectively.